Studies On Local Isolates Of Infectious Bursal Disease Virus - Hashim, Hafizah (1996)

(untitled)
Infectious bursal disease (lBD) is one of the most important viral diseases in chickens. IBD virus ( IBDV) from seven local field outbreaks in layer, broiler and village chickens were isolated, propagated and identified. The pathogenicity and immunogenicity of one of the selected isolates were determined in specific pathogen free (SPF) chickens. The study showed that the IBDV can cause sudden onset of mortality ranging from 15 % to 90 % during the outbreaks.. It occurred in both the vaccinated and non-vaccinated chickens with the age group ranging from 1 8 days to 14 weeks. Layers appeared to be more susceptible to the virus than the broilers, whilst the highest mortality (90 %) was observed in village chickens. Haemorrhages of the bursa of Fabricius, muscles and mucosal layers at the junction of the proventriculus and gizzard were the typical gross lesions caused by the virus. The bursal lesions vary from moderate enlargement and oedematous to severe atrophy. Histologically, the enlarged bursa showed acute necrotizing bursitis, whilst chronic necrotizing bursitis was seen in the atrophic organ. The virus particles were detected in the cytoplasm of the lymphoid cells, macrophages and necrotic cells of the bursa of Fabricius under transmission electron microscopy (TEM). Inoculation of the IBDY isolates obtained from the bursa of Fabricius into embryc'l1ated chicken eggs caused embryonic death, haemorrhages, oedema and hepatic necrosis. The lesions were more severe in SPF eggs than the commercial eggs. Inoculation of the virus into susceptible chickens caused some variation in the mortality and lesions. All isolates of the IBDY from the outbreaks showed distinct curve of agar gel diffusion precipitation lines between the positive sample and reference serum against IBOY.